Dehydrogenation catalyst as well as preparation method and application thereof
By designing a microwave-responsive core-shell structure dehydrogenation catalyst, microwave heating is used to achieve step-by-step coupling effect inside the catalyst particles, solving the problem of poor catalyst stability under high temperature conditions in the prior art, significantly improving the dehydrogenation reaction efficiency and maintaining the stability of the catalyst.
Patent Information
- Application Number
- CN202411412286.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-25
AI Technical Summary
The existing dehydrogenation catalysts work under high temperature conditions, resulting in high energy consumption and poor catalyst stability, limiting the large-scale application of liquid organic hydrogen support hydrogen storage technology.
A microwave-responsive core-shell structure dehydrogenation catalyst is designed. The core uses a high microwave absorption capacity material, the shell uses a conventional dehydrogenation catalyst carrier, and the shell is supported by catalytic active components. The step coupling effect inside the catalyst particles is achieved through microwave heating, and the thermal energy is efficiently transferred to the catalyst active site.
The dehydrogenation reaction efficiency is significantly improved, the catalyst sintering phenomenon is avoided, the good stability and activity of the catalyst is maintained, and the needs of endothermic reaction are met.
Smart Images

Figure CN119500205A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts and relates to a dehydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] my country requires the vigorous development of new energy sources, and hydrogen energy is considered to be an ideal clean energy source due to its many advantages such as high calorific value and net zero emissions. However, hydrogen has the characteristics of low boiling point, low volume density, and flammability and explosion, making its efficient storage and transportation a key technical bottleneck restricting the large-scale application of hydrogen energy. Liquid organic hydrogen carriers (LOHCs) hydrogen storage technology can achieve the storage and release of hydrogen by means of the reversible hydrogenation / dehydrogenation reaction of unsaturated organic matter such as aromatics and hydrogen. Such carriers are liquid at room temperature, have high hydrogen storage density, and are compatible with existing energy infrastructure. Therefore, LOHCs hydrogen storage technology is regarded as a highly promising hydrogen storage method. However, the LOHCs dehydrogenation reaction is a strongly endothermic reaction, and high conversion rate and high dehydrogenation rate can only be achieved under high temperature conditions. However, the high energy consumption caused by high temperature conditions and the poor stability of the catalyst have seriously limited the large-scale application of LOHCs hydrogen storage technology. Therefore, it is of great significance to prepare a dehydrogenation catalyst with good stability and efficiently transfer heat energy to the active sites of the catalyst for efficient dehydrogenation.
[0003] The existing technology mostly adopts fixed bed reactors and adopts the traditional heating method from the outside to the inside. The heat transfer rate is slow. At the same time, cold areas are prone to appear inside the catalyst bed, which will cause the reaction rate to decrease. The higher the degree of dehydrogenation, the stronger the process endothermic effect, which makes the reaction system more severely restricted by low-temperature thermodynamics. Therefore, in order to achieve efficient dehydrogenation under mild conditions, it is necessary to break through the chemical equilibrium and the mass transfer and heat transfer limitations of the reaction process. Microwaves are widely used as a practical means of heat transfer and mass transfer enhancement. Compared with traditional heating, microwave heating does not require heat conduction and directly generates heat inside the material. It has the characteristics of rapid response and high energy utilization. Microwave action is selective and can give priority to fast and uniform heating of materials with good microwave absorption capacity. In the dehydrogenation process of LOHCs, since the reactants and products are generally non-polar or weakly polar, it is difficult to absorb microwaves. Therefore, the microwave field can be used to directly interact with the catalyst to achieve rapid heating of the dehydrogenation reaction, which provides an important innovative path for strengthening the dehydrogenation catalytic reaction. Currently, the most common catalysts used in dehydrogenation reactions use a single microwave absorbing material as a carrier. The "hot spot" effect will cause the overall temperature of the catalyst particles to be too high, resulting in poor controllability and aggregation or sintering of active components.
[0004] Therefore, it is of great significance to develop a dehydrogenation catalyst that has good stability, is not easy to sinter, has high catalytic efficiency and can efficiently transfer heat energy to the active sites of the catalyst. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a dehydrogenation catalyst and a preparation method and application thereof. The dehydrogenation catalyst has a microwave-responsive core-shell structure, and the catalyst carrier structure is designed in layers, and the microwave absorption capacity of the core is greater than that of the shell. By adjusting the microwave absorption capacity of the core material and the shell material, the step coupling effect between the catalyst particles and the microwave field is realized, and the microwave energy is fed in a targeted manner to achieve efficient coordination of heat absorption and heat supply during the dehydrogenation process. When microwave heating is performed, the microwave field directly and quickly supplies heat to the inside of the catalyst, and the microwave absorption material of the core generates heat after absorbing microwaves, which can heat the shell through heat transfer. The shell material and the catalytically active components are stably heated and supplied to the dehydrogenation reaction in time. The heat generation matches the reaction to meet the endothermic reaction requirements, thereby significantly improving the dehydrogenation efficiency. This heating method from the inside to the outside, the temperature distribution inside the catalyst particles is controllable, and the sintering of the catalytically active components on the outer surface of the catalyst can be avoided, so that the catalyst maintains good stability and activity.
[0006] The present invention provides a dehydrogenation catalyst, which comprises a carrier and a catalytically active component supported on the carrier;
[0007] The carrier has a core-shell structure, wherein the core includes a microwave absorbing material, and the shell includes one or more of La2O3, TiO2, Al2O3, SiO2, Fe2O3, MnO2, ZrO2, CeO2, K2O, and MgO, and the microwave absorption capacity of the core is greater than that of the shell.
[0008] The dehydrogenation catalyst as described above, wherein the D50 particle size of the carrier is 20 to 100 nm, and the thickness of the shell is 10 to 50 nm.
[0009] The dehydrogenation catalyst as described above, wherein the dielectric constant of the microwave absorbing material is 1-10.
[0010] The dehydrogenation catalyst as described above, wherein the microwave absorbing material comprises one or more of a carbon-based material, a ferrite material and a transition metal oxide material.
[0011] In the dehydrogenation catalyst as described above, the carbon-based material includes one or more of SiC, activated carbon, graphite and carbon nanotubes.
[0012] The dehydrogenation catalyst as described above, wherein the ferrite material comprises MFe2O4, wherein M is Mn 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ One or more of;
[0013] And / or, the ferrite material includes MFe2O4, wherein M is Mn 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ One or more of;
[0014] And / or, the transition metal oxide material includes one or more of NiO, ZnO, CuO, MnO2, ZrO2, and CeO2.
[0015] The dehydrogenation catalyst as described above, wherein the content of the catalytically active component is 0.1 to 1.0% of the mass of the carrier;
[0016] And / or, the catalytically active components include one or more of Mo, Mn, Fe, Ni, Cu, Sn, Pt, Pb, Ir, Co, Zn, In, Rh, Ru, and Ag.
[0017] The present invention also provides a method for preparing a dehydrogenation catalyst, comprising the following steps:
[0018] 1) coating the shell material on the core by a sol-gel method to obtain the carrier;
[0019] 2) The catalytically active components are loaded on the carrier by an impregnation method to obtain the dehydrogenation catalyst.
[0020] The present invention also provides a method for dehydrogenating an organic liquid hydrogen storage material, comprising the following steps: using the above-mentioned dehydrogenation catalyst to perform dehydrogenation treatment on the organic liquid hydrogen storage material.
[0021] In the dehydrogenation method as described above, the organic liquid hydrogen storage material includes one or more of cyclohexane, methylcyclohexane, toluene, xylene, naphthalene, and methylnaphthalene.
[0022] The dehydrogenation method as described above, wherein the temperature of the dehydrogenation treatment is 270°C to 350°C.
[0023] The implementation of the present invention has at least the following beneficial effects:
[0024] 1) The present invention provides a dehydrogenation catalyst with a core-shell structure, wherein the core is made of microwave absorbing material, the shell is made of conventional dehydrogenation catalyst carrier, and the shell is loaded with catalytically active components. The catalyst promotes the dehydrogenation reaction by microwave heating, changes the energy feed mode, and realizes the synergistic enhancement of the "heat-mass" process. Among them, the heat transfer is embodied in the direct heating of the core by the microwave field, the internal temperature is controllable, sintering is avoided, the good activity and stability of the catalyst can be maintained, and the heat generated can be supplied to the dehydrogenation reaction in time to meet the requirements of the endothermic reaction. The mass transfer is embodied in the temperature distribution of the dehydrogenation catalyst with internal heat and external cold, which is the same as the mass transfer direction of the product hydrogen, which is conducive to the product leaving the reaction system and promoting the reaction to generate hydrogen.
[0025] 2) Based on the microwave absorption capacity of the material, the core-shell structure of the catalyst is designed, the microwave field distribution is regulated, and the catalyst and microwave field are coupled in stages. The microwave field directly heats the inside of the catalyst, and the internal temperature is controllable, which avoids the sintering of the active components on the outer surface of the catalyst and maintains the good activity and stability of the catalyst. In addition, the layered design of the carrier makes the dehydrogenation catalyst have a rich reaction interface, which can reduce the mass transfer resistance and create conditions for the rapid diffusion of hydrogen.
[0026] 3) When the dehydrogenation catalyst of the present invention is applied to the dehydrogenation reaction of organic liquid hydrogen storage materials, its temperature distribution of internal heat and external cold is the same as the mass transfer direction of the product hydrogen, which can make the hydrogen leave the reaction system as soon as possible, create conditions for the rapid diffusion of hydrogen, and promote the reaction in the direction of generating hydrogen, thereby improving the efficiency of the dehydrogenation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic structural diagram of a dehydrogenation catalyst according to an embodiment of the present invention;
[0028] Figure 2 is the XRD spectrum of the Pt-SiC@Al2O3 dehydrogenation catalyst in Example 1 of the present invention;
[0029] Figure 3 This is a comparison chart of the dehydrogenation conversion rate of methylcyclohexane catalyzed by Pt-SiC@Al2O3 at different temperatures in Example 1 and Examples 5-6 of the present invention.
[0030] Description of reference numerals:
[0031] 1- Kernel;
[0032] 2- Shell;
[0033] 3-Catalytically active components. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Organic liquid hydrogen storage materials can achieve the storage and release of hydrogen by means of the reversible hydrogenation / dehydrogenation reaction of unsaturated organic matter such as aromatics with hydrogen. Such carriers are liquid at room temperature, have high hydrogen storage density, and are compatible with existing energy infrastructure. They are considered to be highly promising hydrogen storage carriers. In order to improve the stability of the catalyst and increase the specific surface area, catalyst carriers are often used, such as the skeleton carriers containing alkaline earth metals, Ti and Al, γ-Al2O3 carriers, and encapsulated core-shell structure carriers that have been reported, which have improved the stability of the catalyst to a certain extent. However, the dehydrogenation catalysts loaded by these carriers have the defects of traditional heating mode or single carrier. The traditional heating method from the outside to the inside will cause a cold zone to appear inside the catalyst bed, leading to the occurrence of sintering. The single carrier will lead to an increase in the reaction temperature, which is not conducive to improving the stability and catalytic efficiency of the dehydrogenation catalyst.
[0036] Based on this, the first aspect of the present invention provides a dehydrogenation catalyst, the catalyst comprising a carrier and a catalytically active component supported on the carrier;
[0037] The carrier has a core-shell structure, the core includes microwave absorbing material, and the shell includes one or more of La2O3, TiO2, Al2O3, SiO2, Fe2O3, MnO2, ZrO2, CeO2, K2O, and MgO; the microwave absorption capacity of the core is greater than that of the shell.
[0038] Figure 1 FIG. 1 is a schematic diagram of the structure of a dehydrogenation catalyst according to an embodiment of the present invention. Figure 1As shown, the dehydrogenation catalyst comprises a core 1, a shell 2 and a catalytically active component 3, wherein the outer layer of the core 1 is coated with the shell 2, and the catalytically active component 3 is loaded on the shell 2. The core 1 is a microwave absorbing material, which can be quickly heated when in a microwave field, and the shell 2 is a catalytic carrier material, which can load the catalytically active component, and has good thermal stability, adsorption capacity and a large specific surface area; the catalytically active component 3 on the carrier is a component that plays a dehydrogenation catalytic role. The dehydrogenation catalyst can promote the dehydrogenation reaction by microwave heating. When placed in a microwave field, since the microwave absorption capacity of the core material is greater than that of the shell material, the microwave absorption capacity is successively weakened from the inside to the outside to form a stepped structure, and the microwave field energy is efficiently coupled. Therefore, the microwave absorption material of the core generates heat after absorbing microwaves, and there will be a heat difference between the core and the shell. The heat of the core is gradually transferred to the shell material and the catalytically active component in a manner from the inside to the outside, so that the heating of the catalytically active component is controllable and uniform, and the sintering of the catalytically active component is avoided, so that the catalyst maintains good activity and stability.
[0039] In a specific embodiment, the D50 particle size of the carrier is 20 to 100 nm, specifically 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any two of the above values, and the thickness of the shell is 10 to 50 nm, specifically 10 nm, 20 nm, 30 nm, 40 nm, 50 nm or any two of the above values. The D50 particle size is the average particle size, which can characterize the overall particle size of the carrier. Generally speaking, the smaller the particle size, the larger the specific surface area and the more sufficient the reaction. The shell thickness will affect the heat transfer of the catalytically active components. The inventors have found that the dehydrogenation catalyst with a median particle size D50 of 20 to 100 nm and a shell thickness of 10 to 50 nm has a better dehydrogenation catalytic effect.
[0040] In a specific embodiment, the dielectric constant of the microwave absorbing material is 1 to 10. The dielectric constant can be used as an evaluation standard for the microwave absorption capacity of the material. The dielectric constant will directly affect the material's ability to absorb electromagnetic waves. Generally speaking, materials with higher dielectric constants can absorb microwaves more effectively within certain frequency ranges. If the dielectric constant of the core material is too low, the heat absorbed by the core is not enough to supply the outer shell and catalytic active components, and the efficiency of the dehydrogenation reaction cannot be improved; if the dielectric constant of the core material is too high, the core temperature is too high, and the temperature of the dehydrogenation reaction is often between 300°C and 600°C. Too high a temperature is not conducive to the reaction, and it will also cause a waste of resources. Therefore, controlling the dielectric constant between 1 and 10 is conducive to taking into account the wave absorption performance of the core and the smooth progress of the dehydrogenation reaction.
[0041] In a specific embodiment, the microwave absorbing material of the present invention includes one or more of carbon-based materials, ferrite materials and transition metal oxide materials, all of which have the advantages of good microwave absorbing performance, strong stability and wide sources.
[0042] Furthermore, the carbon-based material includes one or more of silicon carbide, activated carbon, graphite and carbon nanotubes. The carbon-based material has good microwave absorption performance, unique structure, good conductivity, large surface area, and can absorb microwave signals with a wider frequency. The ferrite material includes MFe2O4, where M is Mn 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ One or more of them have the advantages of being able to generate stable magnetic field output and stable physical and chemical properties; the transition metal oxide material includes one or more of NiO, ZnO, CuO, MnO2, ZrO2, and CeO2.
[0043] In a specific embodiment, the catalytically active component content is 0.1-1.0% of the carrier mass. The inventors found that when the catalytically active component content is too low, the catalytically active component loaded on the carrier is too little to catalyze the reaction, and when the catalytically active component content is too high, the catalytically active component will be wasted due to the limited loading capacity of the carrier. When the catalytically active component content is in the range of 0.1-1.0%, the reaction can proceed normally while also achieving the purpose of saving resources.
[0044] The present invention does not specifically limit the type of catalytically active components, as long as the dehydrogenation catalytic reaction can be carried out. In a specific embodiment, the catalytically active components can be one or more of Mo, Mn, Fe, Ni, Cu, Sn, Pt, Pb, Ir, Co, Zn, In, Rh, Ru, and Ag.
[0045] A second aspect of the present invention provides a method for preparing the dehydrogenation catalyst as described above, comprising the following steps:
[0046] 1) coating the shell material on the core by a sol-gel method to obtain the carrier;
[0047] 2) The catalytically active components are loaded on the carrier by an impregnation method to obtain the dehydrogenation catalyst.
[0048] In step 1), the shell is coated on the core by a sol-gel method, which includes the following steps:
[0049] mixing the microwave absorbing material with water to obtain a dispersion;
[0050] Dissolving a first raw material capable of forming a shell precursor in water to form a first solution, dissolving a second raw material capable of forming a shell precursor in water to form a second solution, and dissolving the first solution together with polyethylene glycol to obtain a third solution;
[0051] The second solution and the third solution are added dropwise to the dispersion in parallel to react to obtain a sol containing microwave absorbing material, which is then aged to form a gel. After multiple filtration and water washing, the catalyst carrier precursor is obtained by drying, which is then calcined to obtain the catalyst carrier.
[0052] Specifically, the first raw material and the second raw material are metal salts that can form a shell precursor. Specifically, the first solution and the second solution are metal salt solutions that can form a shell precursor, wherein the first solution reacts with the second solution to generate a metal hydroxide.
[0053] In a specific embodiment, the reaction time is 1 to 3 hours and the reaction temperature is 40 to 80°C.
[0054] In a specific embodiment, the aging time is 6 to 24 hours, and the aging temperature is 80 to 100°C.
[0055] In a specific embodiment, the drying process is carried out at a temperature of 80 to 120° C. and for a time of 10 to 16 hours.
[0056] Specifically, the catalyst carrier precursor also has a core-shell structure, wherein the core is a microwave absorbing material and the shell is a metal hydroxide. After calcination, the metal hydroxide is converted into a metal oxide, thereby forming a catalyst carrier.
[0057] In a specific embodiment, the calcination process includes the following steps: placing the catalyst carrier precursor in a muffle furnace, heating the temperature from room temperature to 400-800° C. at a heating rate of 2-10° C. / min, and keeping the temperature for 6-8 hours.
[0058] Furthermore, in order to make the calcination more complete, the catalyst support precursor may be ground into powder before calcination.
[0059] Optionally, in step 1), the shell material may be coated on the core material by a dissolution method or a template method to obtain a carrier.
[0060] The dissolution method includes the following steps: The dissolution method generally synthesizes a laminated core-shell structure first, and then removes the interlayer template by calcination or dissolution etching to form a hollow core-shell structure. First, SiO2, metal oxide or carbon material is used to wrap the core microwave absorbing material to form the core, and then a suitable dehydrogenation catalyst carrier material is selected as the shell material to wrap the core, and finally the middle layer is removed by calcination or etching to obtain a core-shell catalyst.
[0061] Among them, the template method uses organic molecules (hexadecyltrimethylammonium bromide, polyvinylpyrrolidone) as templates, which self-assemble under the action of non-covalent bonds to form stable structures of different morphologies, so that the precursors that constitute the core layer or shell layer enter the nanoscale interlayer gaps or micropores constructed by these templates to react and obtain the corresponding stacked structure. Finally, the template is selectively removed by calcination to obtain a core-shell catalyst with a stepped pore structure. This pore structure is conducive to the diffusion of larger molecules in and out of it, solving the diffusion limitation problem and increasing the service life of the catalyst.
[0062] In step 2), the catalytically active components are loaded on the carrier by an impregnation method, comprising the following steps: immersing the catalyst carrier in a soluble metal salt solution containing the catalytically active components, drying the catalyst precursor after immersion, grinding and screening the catalyst precursor, and converting the soluble metal salt loaded on the carrier into a metal oxide through a calcination treatment, and then converting the metal oxide into a metal element through a reduction reaction, thereby obtaining a dehydrogenation catalyst.
[0063] Furthermore, in order to allow the soluble metal salt solution containing the catalytically active components to fully adhere to the catalyst support, ultrasonic vibration may be used during the immersion process.
[0064] In a specific embodiment, the drying process is carried out at a temperature of 80 to 120° C. and for a time of 8 to 12 hours.
[0065] In a specific embodiment, the calcination temperature is 400-550° C. and the calcination time is 4-8 hours.
[0066] In a specific embodiment, the reduction reaction includes the following steps: weighing a catalyst precursor and loading it into a reactor, introducing hydrogen, heating to the reaction temperature, reacting at a constant temperature for 3 to 7 hours, stopping the introduction of hydrogen, and cooling to room temperature to obtain a dehydrogenation catalyst.
[0067] The present invention does not specifically limit the type of reactor, which can be selected from conventional reactors in the art capable of loading catalyst precursors, such as a fixed bed reactor.
[0068] In a specific embodiment, the reactor can be equipped with a programmed temperature increasing device to meet the requirement of increasing the temperature at a characteristic rate.
[0069] Further, the reduction reaction temperature is 350-600°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or a range consisting of any two of the above values.
[0070] The third aspect of the present invention provides a dehydrogenation method for an organic liquid hydrogen storage material, comprising the following steps: using the above-mentioned dehydrogenation catalyst to dehydrogenate the organic liquid hydrogen storage material. When the dehydrogenation catalyst of the present invention is applied to the dehydrogenation reaction of the organic liquid hydrogen storage material, its temperature distribution of internal heat and external cold is the same as the mass transfer direction of the product hydrogen, which can make the hydrogen leave the reaction system as soon as possible, create conditions for the rapid diffusion of hydrogen, and promote the reaction in the direction of generating hydrogen, thereby improving the efficiency of the dehydrogenation reaction.
[0071] In a specific embodiment, the dehydrogenation process can be completed by the following steps: the organic liquid hydrogen storage material is passed through a reactor loaded with the dehydrogenation catalyst as described above to perform a dehydrogenation reaction, and the product is collected.
[0072] Furthermore, in order to avoid the influence of other impurities, the organic liquid hydrogen storage material can be mixed with an inert gas and introduced into the reactor. Furthermore, in order to remove the impurity gas in the reactor, the reactor can be purged with an inert gas before the raw material is introduced.
[0073] In a specific embodiment, in order to enable the mixture of the organic liquid hydrogen storage material and the inert gas to quickly reach the reaction temperature, a preheating device may be installed before the reactor to preheat the mixture.
[0074] The present invention does not particularly limit the type of reactor, as long as it has the function of microwave heating. In a specific embodiment, a vertical microwave high temperature reactor can be selected as the reactor.
[0075] Specifically, after the reaction is completed, the product needs to be analyzed, and gas chromatography can be used for qualitative and quantitative analysis.
[0076] Furthermore, the liquid organic hydrogen storage technology achieves hydrogen storage / release by means of hydrogenation / dehydrogenation reactions of unsaturated liquid organics such as certain olefins, alkynes or aromatic hydrocarbons and hydrogen. Unsaturated organic liquids such as olefins, alkynes, and aromatic hydrocarbons can be used as hydrogen storage materials, but considering the energy consumption, hydrogen storage capacity, hydrogen storage agent, and physical properties of the hydrogen storage process, cyclic hydrocarbons are preferred as hydrogen storage agents. Based on this feature, the inventors selected unsaturated organics such as cyclohexane, methylcyclohexane, toluene, xylene, naphthalene, and methylnaphthalene as organic liquid hydrogen storage materials to test the dehydrogenation conversion performance of dehydrogenation catalysts.
[0077] In order to make the dehydrogenation catalytic reaction proceed normally, the dehydrogenation reaction temperature is determined to be 270° C. to 350° C. based on the reaction system and the properties of the catalyst. Exemplarily, the dehydrogenation reaction temperature can be 270° C., 280° C., 290° C., 300° C., 310° C., 320° C., 330° C., 340° C., 350° C. or a range consisting of any two of the above values.
[0078] In a specific embodiment, the space velocity of the catalyst in the dehydrogenation reaction is 6 to 8 h -1 The space velocity of the catalyst within the above range can have both excellent catalytic activity and reaction rate.
[0079] In summary, the present invention provides a dehydrogenation catalyst and a preparation method and application thereof, wherein the dehydrogenation catalyst carrier is prepared into a microwave-responsive core-shell structure, wherein the core is a microwave absorbing material, and the shell carries catalytically active components, wherein the microwave absorption capacity of the core is greater than the microwave absorption capacity of the shell, and the microwave field is used to directly heat the catalyst core, the temperature is controllable and the heat is stable, and the sintering of the catalytically active components on the outer surface of the catalyst is avoided, thereby maintaining the good activity and stability of the catalyst, and the generated heat can be supplied to the dehydrogenation reaction in time to meet the endothermic reaction requirements, thereby significantly improving the dehydrogenation efficiency. The dehydrogenation catalyst of the present invention can effectively improve the catalytic efficiency of the dehydrogenation reaction, and can be widely used in the dehydrogenation process of liquid organic hydrogen storage technology.
[0080] Hereinafter, the dehydrogenation catalyst provided by the present invention and its preparation method and application will be further described in detail through specific examples.
[0081] It should be noted that, in the following examples, unless otherwise specified, the raw materials used can be obtained by commercial purchase or conventional methods, and the experimental methods without specifying specific conditions are conventional methods and conventional conditions well known in the art.
[0082] Example 1
[0083] 1. The preparation method of the dehydrogenation catalyst of this embodiment is as follows:
[0084] 1) Take 400 mg of SiC powder and add it into a reaction beaker containing 200 mL of deionized water as the base liquid;
[0085] 2) 7.93 g Al2(SO4)3 solid was dissolved in 70 mL deionized water to obtain Al2(SO4)3 with a concentration of 0.17 mol / L, 4.2 g polyethylene glycol was added to the above Al2(SO4)3 solution to dissolve, 3.86 g NaAlO2 solid was dissolved in 80 mL water to prepare a NaAlO2 solution with a concentration of 0.78 mol / L, the Al2(SO4)3 solution containing polyethylene glycol and the NaAlO2 solution were added dropwise to a reaction beaker to react, wherein the reaction temperature was 40°C and the reaction time was 1 h, and aging was performed after the reaction, wherein the aging temperature was 80°C and the aging time was 8 h;
[0086] 3) After aging, the mixture was cooled to room temperature naturally, and the solution was filtered and washed with water. After one washing, the filter cake was taken out and placed in a beaker, and deionized water was added and stirred to dissolve the filter cake again. The mixture was stirred for 30 minutes, and filtered again and washed with water for 3 times. The washed filter cake was placed in a crucible and dried in a blast drying oven at 120° C. for 10 hours.
[0087] 4) After drying, the filter cake is ground into powder, placed in a muffle furnace, and heated from room temperature to 500°C at a heating rate of 5°C / min. After constant temperature calcination for 6 hours, the temperature of the muffle furnace is lowered to room temperature to obtain a SiC@Al2O3 catalyst carrier;
[0088] 5) Weigh 1 g of the prepared SiC@Al2O3 catalyst carrier, impregnate the catalyst carrier with 0.6 ml of 0.0935 mol / L chloroplatinic acid solution, use ultrasonic vibration to fully impregnate and adsorb the solution into the interior of the catalyst carrier, and then place the mixture in an oven and dry it at 80°C for 12 h. The obtained solid is ground and sieved, and calcined in a muffle furnace at 400°C for 4 h to obtain a catalyst precursor;
[0089] 6) The catalyst precursor was weighed and loaded into a micro fixed bed reactor. Hydrogen was introduced at a flow rate of 10 mL / min. The programmed temperature rising device of the micro fixed bed reactor was turned on to raise the temperature from room temperature to 400°C. After isothermal reaction for 3 hours, the introduction of hydrogen was stopped and the reactor was cooled to room temperature to finally obtain a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 25.8 nm, a shell thickness of 13.3 nm, and a Pt mass fraction of 0.5%.
[0090] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process comprises the following steps:
[0091] 1) loading more than 0.5 g of a dehydrogenation catalyst into a reactor of a vertical microwave high temperature reaction device, and introducing methylcyclohexane by a plunger pump, wherein the feed amount of methylcyclohexane is 0.1 g / min;
[0092] 2) Before the reaction starts, the preheating device and the reaction device are heated to a reaction temperature of 350°C, and the feed is added after the reaction system is stabilized. Methylcyclohexane is mixed with nitrogen and introduced into the preheating device, and then the temperature is raised to 350°C before entering the reactor. After a period of isothermal reaction, the outlet product is collected and analyzed by a sampling tube every hour, and the methylcyclohexane is analyzed by gas chromatography, and then the dehydrogenation conversion rate and selectivity of the raw material methylcyclohexane are calculated according to the composition.
[0093] The final measured conversion rate of dehydrogenation of methylcyclohexane was 90.39% and the selectivity was 99.9%.
[0094] The dehydrogenation catalyst 0.5% Pt-SiC@Al2O3 of Example 1 above was characterized by XRD. Figure 2 is the XRD spectrum of the Pt-SiC@Al2O3 dehydrogenation catalyst in Example 1 of the present invention, as shown in Figure 2 As shown in Figure 2, the diffraction peaks of Pt-SiC@Al2O3 appear at 36.7°(111) and 41.5°(002), the diffraction peaks of SiC appear at 60.8°(022) and 72.9°(113), and the characteristic peak of Al2O3 appears at 2 θ =37.6°, 46.6° and 66.7°, indicating that SiC and Al2O3 materials were successfully incorporated into the Pt-SiC@Al2O3 catalyst. Figure 2 It can also be seen that the single element Pt in 2 θ The diffraction peaks at 40.2°(111), 46.8°(200) and 68.3°(220) coincide with the main characteristic peaks of the carrier Al2O3, indicating that Pt is successfully loaded on the Pt-SiC@Al2O3 catalyst.
[0095] Example 2
[0096] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0097] In step 5), the catalyst support is impregnated with 0.12 ml of 0.0935 mol / L chloroplatinic acid solution.
[0098] Finally, a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 24.7 nm, a shell thickness of 12.6 nm, and a Pt mass fraction of 0.1% was obtained.
[0099] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0100] The final measured conversion rate of methylcyclohexane dehydrogenation was 77.45% and the selectivity was 99.9%.
[0101] Example 3
[0102] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0103] In step 5), the catalyst support is impregnated with 0.36 ml of 0.0935 mol / L chloroplatinic acid solution.
[0104] Finally, a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 24.8 nm, a shell thickness of 12.8 nm, and a Pt mass fraction of 0.3% was obtained.
[0105] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0106] The final measured conversion rate of dehydrogenation of methylcyclohexane was 86.26%, and the selectivity was 99.9%.
[0107] Example 4
[0108] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0109] In step 5), the catalyst support is impregnated with 0.84 ml of 0.0935 mol / L chloroplatinic acid solution;
[0110] Finally, a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 26.7 nm, a shell thickness of 13.4 nm, and a Pt mass fraction of 0.7% was obtained.
[0111] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0112] The final measured conversion rate of dehydrogenation of methylcyclohexane was 91.02% and the selectivity was 99.9%.
[0113] In order to compare the effect of Pt content on the average conversion rate and selectivity of the dehydrogenation reaction of the dehydrogenation catalyst of the present invention, the average conversion rate and selectivity information of the dehydrogenation reaction of Examples 1-4 are shown in Table 1:
[0114] Table 1
[0115]
[0116] The above results show that:
[0117] As the mass fraction of Pt increases from 0.1% to 0.7%, the selectivity reaches 99.9%, indicating that Pt-SiC@Al2O3 catalysts with different Pt contents have good selectivity for the dehydrogenation reaction with methylcyclohexane as substrate;
[0118] When the mass fraction of Pt increases gradually, the dehydrogenation conversion rate of methylcyclohexane gradually increases. When the mass fraction of Pt increases from 0.1% to 0.5%, the growth rate of the dehydrogenation conversion rate is fast, but when the mass fraction of Pt increases from 0.5% to 0.7%, the dehydrogenation conversion rate only increases slightly; when the mass fraction of Pt increases from 0.5% to 0.7%, the dehydrogenation conversion rate of methylcyclohexane does not increase significantly;
[0119] As the mass fraction of Pt increases, the D50 and shell thickness values of the catalyst fluctuate only slightly, indicating that the change in the mass fraction of Pt in this experiment has no significant effect on the D50 particle size and shell thickness of the catalyst.
[0120] Example 5
[0121] 1. The preparation method of the dehydrogenation catalyst in this embodiment is the same as that in Example 1, and finally a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 33.4 nm, a shell thickness of 16.2 nm, and a Pt mass fraction of 0.5% is obtained.
[0122] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane. The process is basically the same as that in Example 1, except that:
[0123] In step 2), the preheating device and the reaction device are heated to a reaction temperature of 300° C. before the reaction starts, and the feed is added after the reaction system is stabilized. Methylcyclohexane is mixed with nitrogen and introduced into the preheating device, and then enters the reactor after the temperature rises to 300° C. After a period of isothermal reaction, the outlet product is collected and analyzed by a sampling tube every hour, and the methylcyclohexane is analyzed by gas chromatography, and then the dehydrogenation conversion rate and selectivity of the raw material methylcyclohexane are calculated according to the composition.
[0124] The final measured conversion rate of methylcyclohexane dehydrogenation was 62.23% and the selectivity was 99.9%.
[0125] Example 6
[0126] 1. The preparation method of the dehydrogenation catalyst in this embodiment is the same as that in Example 1, and finally a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 39.8 nm, a shell thickness of 19.1 nm, and a Pt mass fraction of 0.5% is obtained.
[0127] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane. The process is basically the same as that in Example 1, except that:
[0128] In step 2), the preheating device and the reaction device are heated to a reaction temperature of 350° C. before the reaction starts, and the feed is added after the reaction system is stabilized. Methylcyclohexane is mixed with nitrogen and introduced into the preheating device, and then the temperature is raised to 350° C. and then the reactor is entered. After a period of isothermal reaction, the outlet product is collected and analyzed by a sampling tube every hour, and the methylcyclohexane is analyzed by gas chromatography, and then the dehydrogenation conversion rate and selectivity of the raw material methylcyclohexane are calculated according to the composition.
[0129] The final measured conversion rate of methylcyclohexane dehydrogenation was 78.25% and the selectivity was 99.9%.
[0130] In order to compare the effect of temperature on the average conversion rate and selectivity of the dehydrogenation reaction of the dehydrogenation catalyst of the present invention, the average conversion rate and selectivity information of the dehydrogenation reaction of Example 1 and Examples 5-6 are shown in Table 2:
[0131] Table 2
[0132]
[0133] The above results show that the average conversion rate increases from 62.23% to 90.39% when the temperature increases from 300℃ to 350℃. Figure 3 It can be seen that the average conversion rate of the 0.5% Pt-SiC@Al2O3 dehydrogenation catalyst increases with increasing temperature, and the selectivity does not change significantly, indicating that the dehydrogenation efficiency of the dehydrogenation catalyst of the present invention is improved with increasing temperature while maintaining a high selectivity.
[0134] Example 7
[0135] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0136] In step 2), 38.29 g of Al2(SO4)3 solid is dissolved in 300 mL of deionized water to obtain Al2(SO4)3 with a concentration of 0.1915 mol / L, 4.2 g of polyethylene glycol is added to the above Al2(SO4)3 solution to dissolve, 14.57 g of NaAlO2 solid is dissolved in 150 ml of water to prepare a NaAlO2 solution with a concentration of 1.1850 mol / L, the Al2(SO4)3 solution containing polyethylene glycol and the NaAlO2 solution are added dropwise to the reaction beaker in parallel to react, wherein the reaction temperature is 40°C and the reaction time is 1 h, and aging is carried out after the reaction, wherein the aging temperature is 80°C and the aging time is 8 h.
[0137] Finally, a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 80.8 nm, a shell thickness of 39.2 nm, and a Pt mass fraction of 0.5% was obtained.
[0138] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0139] The final measured conversion rate of dehydrogenation of methylcyclohexane was 31.6%, and the selectivity was 99.9%.
[0140] Example 8
[0141] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0142] In step 2), 3.78 g of Al2(SO4)3 solid is dissolved in 70 mL of deionized water to obtain Al2(SO4)3 with a concentration of 0.0810 mol / L, 4.2 g of polyethylene glycol is added to the above Al2(SO4)3 solution to dissolve, 1.84 g of NaAlO2 solid is dissolved in 80 ml of water to prepare a NaAlO2 solution with a concentration of 0.2806 mol / L, the Al2(SO4)3 solution containing polyethylene glycol and the NaAlO2 solution are added dropwise to the reaction beaker in parallel to react, wherein the reaction temperature is 40°C and the reaction time is 1 h, and aging is carried out after the reaction, wherein the aging temperature is 80°C and the aging time is 8 h.
[0143] Finally, a Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 9.7 nm, a shell thickness of 4.8 nm, and a Pt mass fraction of 0.5% was obtained.
[0144] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0145] The final measured conversion rate of dehydrogenation of methylcyclohexane was 20.3% and the selectivity was 99.9%.
[0146] Example 9
[0147] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0148] In step 1), 80 mg of activated carbon powder was added to a reaction beaker containing 200 mL of deionized water as a base solution;
[0149] Finally, a Pt-activated carbon@Al2O3 catalyst sample with a D50 particle size of 24.8 nm, a shell thickness of 11.8 nm, and a Pt mass fraction of 0.5% was obtained.
[0150] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0151] The final measured conversion rate of methylcyclohexane dehydrogenation was 52.83% and the selectivity was 99.9%.
[0152] In order to compare the effects of D50 particle size, shell thickness and dielectric constant of the core material on the average conversion rate and selectivity of the dehydrogenation reaction of the dehydrogenation catalyst of the present invention, the average conversion rate and selectivity of the dehydrogenation reaction of Example 1 and Examples 7-11 are shown in Table 3:
[0153] Table 3
[0154]
[0155] The above results show that, from Example 1 and Implementation 7-8, when the D50 particle size is within the range of 70 to 100 nm, as the D50 particle size and shell thickness increase, the average conversion of the dehydrogenation catalyst first increases and then decreases, indicating that the D50 particle size and shell thickness are too large or too small, the dehydrogenation efficiency of the dehydrogenation catalyst will be reduced, while the selectivity is always maintained at 99.9%, indicating that there is no effect on the selectivity; Comparing Example 1 with Example 9, it can be seen that when the core microwave absorbing material is replaced by SiC with a larger dielectric constant with activated carbon with a smaller dielectric constant, the average conversion rate of the dehydrogenation catalyst is reduced, but the selectivity has no obvious change, indicating that the dielectric constant of the core absorbing material will affect the dehydrogenation efficiency, but has no effect on the selectivity of the dehydrogenation catalyst. It can be seen that the particle size of the dehydrogenation catalyst D50, the shell thickness, and the dielectric constant of the core material of the present invention will affect the dehydrogenation catalytic efficiency, but will not affect the selectivity of the dehydrogenation catalyst for methylcyclohexane.
[0156] Example 10
[0157] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0158] In step 1), 400 mg of MnFe2O4 was added to 200 ml of deionized water as the base solution.
[0159] Finally, a Pt-MnFe2O4@Al2O3 catalyst sample was obtained with a D50 particle size of 42.12 nm, a shell thickness of 20.47 nm, and a Pt mass fraction of 0.5%.
[0160] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0161] The final measured conversion rate of dehydrogenation of methylcyclohexane was 92.36%, and the selectivity was 99.9%.
[0162] Embodiment 11
[0163] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0164] In step 1), 400 mg of MgO was added to 200 ml of deionized water as a base solution.
[0165] Finally, a Pt-MgO@Al2O3 catalyst sample with a D50 particle size of 38.21 nm, a shell thickness of 18.17 nm, and a Pt mass fraction of 0.5% was obtained.
[0166] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0167] The final measured conversion rate of methylcyclohexane dehydrogenation was 90.28% and the selectivity was 99.9%.
[0168] Example 12
[0169] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0170] In step 2), 30 ml of 0.3874 mol / L Ce(NO3)3·6H2O solution is added to a beaker, 0.28 g of polyethylene glycol is added to the Ce(NO3)3·6H2O solution, and dispersed under ultrasound for 10 minutes until the polyethylene glycol is completely dissolved in the solution, and then the mixed liquid is stirred at 300 rpm for 1 hour at room temperature and pressure. Take 20 mL of 25% ammonia water, add 50 mL of deionized water to the ammonia water to dilute it, and add the diluted ammonia water dropwise to the mixed liquid at a rate of 1 mL / min. During the dropping process, the mixed liquid still maintains a stirring speed of 300 rpm. While dropping, the pH of the mixed liquid is tested with a pH meter. Stop dropping when the pH value is 9, and age after stirring for 2 hours, wherein the aging temperature is 80°C and the aging time is 10 hours;
[0171] Finally, a Pt-SiC@CeO2 catalyst sample with a D50 particle size of 26.53 nm, a shell thickness of 11.20 nm, and a Pt mass fraction of 0.5% was obtained.
[0172] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0173] The final measured conversion rate of dehydrogenation of methylcyclohexane was 94.54% and the selectivity was 99.9%.
[0174] Embodiment 13
[0175] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0176] In step 5), 1 g of the prepared SiC@Al2O3 catalyst carrier is weighed, and the catalyst carrier is impregnated with 2 ml of a 0.8425 mol / L Ni(NO3)2·6H2O solution. Ultrasonic vibration is used to fully impregnate and adsorb the solution into the interior of the catalyst carrier. The mixture is then placed in an oven and dried at 80°C for 12 h. The resulting solid is ground and sieved, and calcined in a muffle furnace at 400°C for 4 h to obtain a catalyst precursor.
[0177] Finally, a Ni-SiC@Al2O3 catalyst sample with a D50 particle size of 28.15 nm, a shell thickness of 13.46 nm, and a Ni mass fraction of 10% was obtained.
[0178] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0179] The final measured conversion rate of methylcyclohexane dehydrogenation was 83.78% and the selectivity was 99.9%.
[0180] Embodiment 14
[0181] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, except that:
[0182] In step 5), 1 g of the prepared SiC@Al2O3 catalyst carrier is weighed, and the catalyst carrier is impregnated with 2 ml of a CuSO4·5H2O solution with a concentration of 0.3925 mol / L. Ultrasonic vibration is used to fully impregnate and adsorb the solution into the interior of the catalyst carrier. The mixture is then placed in an oven and dried at 80°C for 12 h. The obtained solid is ground and sieved, and calcined in a muffle furnace at 400°C for 4 h to obtain a catalyst precursor.
[0183] Finally, a Cu-SiC@Al2O3 catalyst sample with a D50 particle size of 26.58 nm, a shell thickness of 12.66 nm, and a Cu mass fraction of 5% was obtained.
[0184] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the treatment process is the same as that in Example 1.
[0185] The final measured conversion rate of methylcyclohexane dehydrogenation was 85.26%, and the selectivity was 99.9%.
[0186] In order to compare the effects of the core material, shell material and catalytically active components on the average conversion rate and selectivity of the dehydrogenation reaction of the dehydrogenation catalyst of the present invention, the average dehydrogenation catalyst and selectivity results of Example 1 and Implementations 12-16 are shown in Table 4:
[0187] Table 4
[0188]
[0189] The above results show that, under the premise that the dielectric constant of the shell material is greater than the dielectric constant of the core microwave absorbing material, when the core material of the dehydrogenation catalyst is carbon-based material, ferrite material and transition metal oxide material, the shell material is Al2O3, CeO2, and the catalytic active components are Ni and Cu, the dehydrogenation catalyst of the present invention has good conversion rate and selectivity. It is also found that when the core microwave absorbing material is MgO, the dehydrogenation catalyst also maintains a relatively high average conversion rate and selectivity.
[0190] Embodiment 15
[0191] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, and finally a 0.5% Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 25.8 nm and a shell thickness of 13.3 nm is obtained.
[0192] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate toluene, and the treatment process is the same as that in Example 1.
[0193] The final measured conversion rate of toluene / xylene dehydrogenation was 87.56% and the selectivity was 99.9%.
[0194] Example 16
[0195] 1. The preparation method of the dehydrogenation catalyst in this embodiment is basically the same as that in Example 1, and finally a 0.5% Pt-SiC@Al2O3 catalyst sample with a D50 particle size of 25.8 nm and a shell thickness of 13.3 nm is obtained.
[0196] 2. Adopt above-mentioned dehydrogenation catalyst to dehydrogenate naphthalene, and the processing process is the same as embodiment 1.
[0197] The final measured naphthalene / methylnaphthalene conversion was 82.46% and the selectivity was 99.9%.
[0198] In order to compare the dehydrogenation catalytic effects of the dehydrogenation catalyst of the present invention on different organic liquid hydrogen storage materials, the average dehydrogenation catalyst and selectivity results of Example 1 and Implementations 17-18 are shown in Table 5:
[0199] Table 5
[0200]
[0201] The above results show that the average conversion rate of the dehydrogenation catalyst of the present invention for toluene dehydrogenation reaction is 87.56% and the selectivity is 99.9%, and the average conversion rate of the dehydrogenation reaction for naphthalene is 82.46% and the selectivity is 99.9%, indicating that the catalyst of the present invention also has good conversion rate and selectivity for toluene and naphthalene.
[0202] Comparative Example 1
[0203] 1. The dehydrogenation catalyst carrier of this comparative example is a single carrier Al2O3, that is, Pt is directly loaded on Al2O3, and the preparation method is as follows:
[0204] 1) 7.93 g Al2(SO4)3 solid was dissolved in 70 mL deionized water to obtain Al2(SO4)3 with a concentration of 0.17 mol / L, 4.2 g polyethylene glycol was added to the above Al2(SO4)3 solution to dissolve, 3.86 g NaAlO2 solid was dissolved in 80 mL water to prepare a NaAlO2 solution with a concentration of 0.78 mol / L, the Al2(SO4)3 solution containing polyethylene glycol and the NaAlO2 solution were added dropwise to a reaction beaker to react, wherein the reaction temperature was 40°C and the reaction time was 1 h, and aging was performed after the reaction, wherein the aging temperature was 80°C and the aging time was 8 h;
[0205] 2) After aging, the mixture was cooled to room temperature naturally, and the solution was filtered and washed with water. After one washing, the filter cake was taken out and placed in a beaker. Deionized water was added and stirred to dissolve the filter cake again. The stirring time was 30 minutes. The mixture was filtered again and washed with water for 3 times. The washed filter cake was placed in a crucible and dried in a 120° C. forced air drying oven for 10 hours.
[0206] 3) After drying, the filter cake is ground into powder, placed in a muffle furnace, and heated from room temperature to 500°C at a heating rate of 5°C / min. After calcination at a constant temperature for 6 hours, the temperature of the muffle furnace is raised to room temperature to obtain an Al2O3 catalyst carrier;
[0207] 4) Weigh 1 g of the prepared Al2O3 catalyst carrier, impregnate the catalyst carrier with 0.12 ml of 0.0935 mol / L chloroplatinic acid solution, perform ultrasonic vibration to fully impregnate and adsorb the solution into the interior of the carrier, and then place the mixture in an oven at 80°C for 12 h. After grinding and sieving the obtained solid, calcine it in a muffle furnace at 400°C for 4 h to obtain a catalyst precursor;
[0208] 5) Weigh the catalyst precursor, load it into a micro fixed bed reactor, introduce hydrogen at a flow rate of 10 mL / min, turn on the programmed temperature rising device of the micro fixed bed reactor to raise the temperature from room temperature to 400°C, and stop introducing hydrogen after isothermal reaction for 3 hours, and cool to room temperature to obtain a catalyst sample 0.1% Pt-Al2O3.
[0209] 2. The above-mentioned 0.1% Pt-Al2O3 dehydrogenation catalyst was used to dehydrogenate methylcyclohexane. The dehydrogenation reaction process was the same as that in Example 1.
[0210] The final measured conversion rate of methylcyclohexane dehydrogenation was 62.6% and the selectivity was 99.9%.
[0211] Comparative Example 2
[0212] 1. The preparation method of the dehydrogenation catalyst in the embodiment is the same as that in the comparative example 1, except that:
[0213] In step 4), the catalyst support is impregnated with 0.36 ml of 0.0935 mol / L chloroplatinic acid solution.
[0214] Finally, a 0.3% Pt-Al2O3 catalyst sample was obtained.
[0215] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the dehydrogenation reaction process is the same as that in Example 1.
[0216] The final measured conversion rate of dehydrogenation of methylcyclohexane was 71.25% and the selectivity was 99.9%.
[0217] Comparative Example 3
[0218] 1. The preparation method of the dehydrogenation catalyst in the embodiment is the same as that in the comparative example 1, except that:
[0219] In step 4), the catalyst support is impregnated with 0.6 ml of 0.0935 mol / L chloroplatinic acid solution.
[0220] Finally, a 0.5% Pt-Al2O3 catalyst sample was obtained.
[0221] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the dehydrogenation reaction process is the same as that in Example 1.
[0222] The final measured conversion rate of methylcyclohexane dehydrogenation was 75.68% and the selectivity was 99.9%.
[0223] Comparative Example 4
[0224] 1. The preparation method of the dehydrogenation catalyst in the embodiment is basically the same as that in the comparative example 1, except that:
[0225] In step 4), the catalyst support is impregnated with 0.96 ml of 0.0935 mol / L chloroplatinic acid solution.
[0226] Finally, a 0.8% Pt-Al2O3 catalyst sample was obtained.
[0227] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the dehydrogenation reaction process is the same as that in Example 1.
[0228] The final measured conversion rate of methylcyclohexane dehydrogenation was 88.89% and the selectivity was 99.9%.
[0229] Comparative Example 5
[0230] 1. The dehydrogenation catalyst carrier of this comparative example is a single carrier CeO2, that is, Pt is directly loaded on CeO2, and the preparation method is as follows:
[0231] 1) Take 30ml of 0.3874mol / L Ce(NO3)3·6H2O solution and add it to a beaker, add 0.28g of polyethylene glycol to the Ce(NO3)3·6H2O solution, disperse it under ultrasound for 10min until the polyethylene glycol is completely dissolved in the solution, and then stir the mixed liquid at 300rpm for 1h at room temperature and pressure. Take 20mL of 25% ammonia water, add 50mL of deionized water to dilute the ammonia water, and add the diluted ammonia water dropwise to the mixed liquid at a rate of 1mL / min. During the dropping process, the mixed liquid still maintains a stirring speed of 300rpm. While dropping, use a pH meter to test the pH of the mixed liquid. Stop dropping when the pH value is 9, and age after stirring for 2h, wherein the aging temperature is 80℃ and the aging time is 8h;
[0232] 2) After aging, the mixture was cooled to room temperature naturally, and the solution was filtered and washed with water. After one washing, the filter cake was taken out and placed in a beaker. Deionized water was added and stirred to dissolve the filter cake again. The stirring time was 30 minutes. The mixture was filtered again and washed with water for 3 times. The washed filter cake was placed in a crucible and dried in a 120° C. forced air drying oven for 10 hours.
[0233] 3) After drying, the filter cake is ground into powder, placed in a muffle furnace, and heated from room temperature to 400°C at a heating rate of 5°C / min. After calcination at a constant temperature for 6 hours, the temperature of the muffle furnace is raised to room temperature, thereby obtaining a CeO2 catalyst carrier;
[0234] 4) Weigh 1 g of the prepared CeO2 catalyst carrier, impregnate the catalyst carrier with 0.12 ml of 0.0935 mol / L chloroplatinic acid solution, and use ultrasonic vibration to fully impregnate and adsorb the solution into the interior of the carrier. Then, place the mixture in an oven at 80°C and dry it for 12 h. After grinding and sieving the obtained solid, calcine it in a muffle furnace at 400°C for 4 h to obtain a catalyst precursor;
[0235] 5) Weigh the catalyst precursor, load it into a micro fixed bed reactor, introduce hydrogen at a flow rate of 10 mL / min, turn on the programmed temperature rising device of the micro fixed bed reactor to raise the temperature from room temperature to 400°C, and stop introducing hydrogen after isothermal reaction for 3 hours. Cool it to room temperature to obtain a catalyst sample 0.1% Pt-CeO2.
[0236] 2. The above-mentioned dehydrogenation catalyst is used to dehydrogenate methylcyclohexane, and the dehydrogenation reaction process is the same as that in Example 1.
[0237] The final measured conversion rate of methylcyclohexane dehydrogenation was 78.61% and the selectivity was 99.9%.
[0238] Test Case
[0239] The following parameters were tested on the dehydrogenation catalysts prepared in Examples 1-4 and Comparative Examples 1-2:
[0240] 1. Chlorine content
[0241] Test method:ICP.
[0242] 2. Specific surface area
[0243] Test method:BET.
[0244] 3. Kong Rong
[0245] Test method:BET.
[0246] 4. Aperture
[0247] Test method:BET.
[0248] The test results of the chlorine content, specific surface area, pore volume and pore diameter of the dehydrogenation catalyst in the above test examples are shown in Table 6.
[0249] Table 6
[0250]
[0251] The above results show that, as can be seen from Examples 1-4, as the mass fraction of Pt increases, the specific surface area, pore size, and pore volume have almost no significant changes; it can be seen from Examples 1-5 and Comparative Examples 1-4 that, relative to the catalyst with a single carrier, the specific surface area, pore volume, and pore size of the core-shell structure catalyst in the present invention are larger, and the increase in specific surface area, pore volume, and pore size is often conducive to improving the dispersion of the catalytically active components on the surface of the catalyst carrier, which can improve the efficiency of the dehydrogenation reaction. It can be seen from Comparative Examples 1 and 5 that compared with the dehydrogenation catalyst with Al2O3 as the single carrier, the dehydrogenation catalyst with CeO2 as the single carrier has a smaller specific surface area, pore volume, and pore size, but its dehydrogenation conversion rate is higher, and there is no significant difference in selectivity.
[0252] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A dehydrogenation catalyst, characterized in that The catalyst comprises a carrier and a catalytically active component supported on the carrier; The carrier has a core-shell structure, wherein the core includes a microwave absorbing material, and the shell includes one or more of La2O3, TiO2, Al2O3, SiO2, Fe2O3, MnO2, ZrO2, CeO2, K2O, and MgO, and the microwave absorption capacity of the core is greater than that of the shell.
2. The dehydrogenation catalyst according to claim 1, characterized in that The D50 particle size of the carrier is 20-100 nm, and the thickness of the shell is 10-50 nm.
3. The dehydrogenation catalyst according to claim 1 or 2, characterized in that The dielectric constant of the microwave absorbing material is 1-10.
4. The dehydrogenation catalyst according to claim 3, characterized in that The microwave absorbing material includes one or more of a carbon-based material, a ferrite material, and a transition metal oxide material.
5. The dehydrogenation catalyst according to claim 4, characterized in that The carbon-based material includes one or more of SiC, activated carbon, graphite and carbon nanotubes; And / or, the ferrite material includes MFe2O4, wherein M is Mn 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ One or more of; And / or, the transition metal oxide material includes one or more of NiO, ZnO, CuO, MnO2, ZrO2, and CeO2.
6. The dehydrogenation catalyst according to any one of claims 1 to 5, characterized in that The content of the catalytically active component is 0.1 to 1.0% of the mass of the carrier; And / or, the catalytically active components include one or more of Mo, Mn, Fe, Ni, Cu, Sn, Pt, Pb, Ir, Co, Zn, In, Rh, Ru, and Ag.
7. A method for preparing the dehydrogenation catalyst according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) coating the shell material on the core by a sol-gel method to obtain the carrier; 2) The catalytically active components are loaded on the carrier by an impregnation method to obtain the dehydrogenation catalyst.
8. A method for dehydrogenating an organic liquid hydrogen storage material, characterized in that: The method comprises the following steps: using the dehydrogenation catalyst described in any one of claims 1 to 6 to perform dehydrogenation treatment on the organic liquid hydrogen storage material.
9. The dehydrogenation method according to claim 8, characterized in that: The organic liquid hydrogen storage material includes one or more of cyclohexane, methylcyclohexane, toluene, xylene, naphthalene and methylnaphthalene.
10. The dehydrogenation method according to claim 8 or 9, characterized in that: The temperature of the dehydrogenation treatment is 270°C to 350°C.
Citation Information
Cited By
Core-shell structure catalyst as well as preparation method and application thereof
CN120550794A
A core-shell structure catalyst and a preparation method and application thereof
CN120550794B